Comparison between Bolus Intracoronary versus Bolus Intravenous Injection Regimens of Eptifibatide during Primary Percutaneous Coronary Intervention in Patients with Anterior ST-Segment Elevation Myocardial Infarction - Mohamed Hassan Nab; Shaimaa Mostafa; Khaled Elrabat; Hamza Kabil; Neama Elmelegy (Рациональная фармакотерапия в кардиологии, 2019)
Background. Eptifibatide achieves high local concentration via direct intracoronary (I/V) injection as it promotes clot disaggregation, but it remains unclear if it is of superior benefit than the routine intravenous (I/V) administration. Aim. The current study aimed to examine the safety and efficacy of I/C vs I/V bolus regimen dose of eptifibatide during primary percutaneous coronary intervention (PPCI).Material and methods. Prospective, controlled, randomized study enrolled 100 patients with acute anterior ST-segment elevation myocardial infarction (STEMI) eligible for PPCI equally divided into 2 groups (group A received bolus I/C eptifibatide and group B received it I/V) followed by 12-hour continuous I/V infusion. Features related to of myocardial salvage in the form of TIMI flow grade 3, myocardial blush grade 3, ST segment resolution and left ventricular systolic function were evaluated with short-term follow up for 1 month.Results. Mean age of the study population was 50.95±8.45years, there was statistically insignificant difference between both groups regarding baseline characteristics in age (p=0.062), gender (p=0.488), coronary artery disease risk factors (p>0.05), time from onset of pain to admission (p=0.86) or door to balloon (p=0.12). Group A achieved statistically significant better myocardial blush grade 3 (42% vs 10%, p=0.005), ejection faction 30 days after PPCI (46.11±7.81% vs 40.88±6.26%, p=0.005) but statistically insignificant TIMI flow grade 3 (p=0.29) and ST resolution (p=0.34). Incidence of complications in the hospital and 30 days after discharge was statistically insignificant (p>0.05).Conclusion. Both regimens were safe and effective in STEMI patients undergoing PPCI and regimen of I/C bolus eptifibatide achieved better myocardial blush grade and systolic function.